Method for preparing supported MOF (Metal Organic Framework) membrane through induction of low-crystal aggregation state structure, MOF membrane and application
By depositing Al-MOF seeds on the porous support and induced to grow into low-crystalline aggregate layers with supersaturated solutions, the problem of difficult to prepare dense high-priced metal MOF films in the prior art is solved, and efficient molecular scale is achieved Separation performance.
Patent Information
- Application Number
- CN202411069525.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-08-06
AI Technical Summary
The prior art is difficult to prepare dense high-valent metal MOF film materials, resulting in limited separation performance in molecular-scale separation systems.
By depositing Al-MOF seeds on the porous support, the seeds are induced to grow into a continuous low-crystalline aggregate layer by using a supersaturated solution and converted into a dense MOF film by further crystallization reaction.
The preparation of dense and defect-free high-valent metal MOF film is achieved, which significantly improves its separation performance and structural stability in molecular-scale separation systems.
Smart Images

Figure CN119463234A_ABST
Abstract
Description
Technical Field
[0001] The present invention specifically relates to a method for preparing a supported MOF membrane by inducing a low-crystalline aggregated structure, a MOF membrane and applications. Background Art
[0002] Sub-nanoscale separation processes, including the selective transfer and separation of gases and liquids, play a key role in catalysis, energy, material conversion and other systems. Traditional separation technologies such as distillation and absorption are complex to operate, with high energy consumption and carbon emission intensity, while membrane separation technology is green, safe, and efficient. Membrane separation is not limited by thermodynamic equilibrium and has the advantages of reduced investment and operating costs, energy saving and consumption reduction, and process intensification brought about by integration effects.
[0003] Membrane materials are the core of membrane separation technology. Polymer membrane materials have promoted the development of membrane technology application system from micrometer scale to nanometer scale. However, facing the demand for sub-nanometer molecular separation, the existing commercial polymer membrane materials cannot meet the requirements of industrial application due to their structural limitations, which greatly restricts their research and application in the field of molecular scale separation membranes.
[0004] Metal-organic framework (MOF) is a new type of porous crystalline material composed of metal ions or ion clusters coordinated with organic ligands. Compared with traditional zeolite molecular sieve materials, MOF not only has regular nanochannels, but also, the pore size of MOF can be designed and precisely adjusted at the sub-nanometer scale.
[0005] High-stability MOFs formed by coordination of high-valent metal cations and carboxylic acid organic ligands have excellent thermal, chemical and mechanical stability. The MOF membranes precisely constructed with them are expected to meet the precise and stable separation requirements of molecular-scale separation systems. However, most of the prior art is divalent and other low-valent MOF materials, such as Al-MOF, which is the most common, while trivalent and other high-valent metal MOF materials such as Al-MOF materials are relatively rare. The reason may be that the seeds of Al-based MOF materials are easy to grow into rods, and their growth rates on each direction axis are inconsistent, making it difficult to form a dense MOF material film. That is, the nucleation energy barrier of high-valent MOF crystals such as Al-MOF materials is high, and it is difficult to accurately control and balance the nucleation rate and growth direction of MOF, and the topological morphology is mostly anisotropic rod-shaped crystals, which makes it difficult for crystal growth to coexist, and inevitably produces grain boundary defects, which seriously weakens the intrinsic separation performance of the membrane material.
[0006] Therefore, it is still challenging to prepare high-valent MOF membranes based on current technology. The grain boundary symbiosis of the membrane is poor, and the resulting grain boundary defects limit the intrinsic separation performance of the MOF pores. It is even more difficult to coordinately regulate the pore orientation of the MOF membrane, and the membrane separation performance needs to be further improved. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a supported MOF membrane by inducing a low-crystalline aggregate structure, which can prepare a dense high-valent metal MOF crystal membrane material, and the membrane material can be used for efficient separation of various molecular scale separation systems.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] A method for preparing an Al-MOF membrane material comprises the following steps: 1) depositing Al-MOF seed crystals on the surface of a porous support to obtain an Al-MOF seed crystal layer; 2) placing the porous support with the Al-MOF seed crystal layer deposited on the surface in a supersaturated solution for reaction to grow a continuous low-crystalline Al-MOF aggregate layer on the surface of the porous support; 3) subjecting the porous support with the continuous low-crystalline Al-MOF aggregate layer grown on the surface to a crystallization reaction to obtain the Al-MOF membrane material; the supersaturated solution comprises an aluminum salt, a ligand and a coordination regulator.
[0010] In the present invention, a supersaturated solution refers to a solution in which the amount of solute exceeds its saturated solubility. For example, in the supersaturated solution, the amount of aluminum salt, ligand and ligand regulator dissolved exceeds their respective saturated solubility.
[0011] In the prior art, most MOF membrane materials are divalent MOF materials, such as Zn-MOF materials. When divalent MOF materials form crystals, it is easy to control their nucleation rate and crystal growth direction, and it is easy to make the rates in each growth direction similar, so that it is easy to obtain spherical crystal nuclei, which continue to grow and easily grow into continuous MOF membranes. However, for trivalent and other high-valent MOF materials such as Al-MOF materials, the nucleation energy barrier is high, and it is difficult to accurately control and balance the nucleation rate and growth direction of MOF, and the topological morphology is mostly anisotropic rod-shaped crystals, which makes it difficult for crystal growth to coexist, and it is difficult to form a continuous and dense membrane, which makes it easy for the membrane material to have defects, and thus significantly affects its separation performance.
[0012] The inventors of this application have found through research that a seed layer is first deposited on a porous carrier, and then the method provided by the present invention uses the supersaturated crystallization principle to induce the seed to first grow into a continuous low-crystalline aggregate layer, and then further crystallize the low-crystalline aggregate to achieve the transformation of "continuous low-crystalline film-continuous MOF crystalline film", thereby preparing a dense and defect-free MOF film. This two-step reaction corresponds to the nucleation and growth of the crystal, making the crystal growth behavior of MOF highly controllable, thereby realizing the preparation of high-performance MOF membranes.
[0013] In the prior art, for divalent MOF materials, although the seed growth method is usually used to synthesize MOF membranes, the pre-coated or deposited seeds are in a dispersed state, not in a continuous state, that is, the seed method of the prior art grows a continuous final MOF membrane once, and does not involve the transitional morphology of the low crystalline aggregate layer of the present application. Using the traditional seed growth method, it is impossible to prepare a continuous and dense film layer of a high-valent MOF.
[0014] In some embodiments, the aluminum salt is selected from a combination of one or more of aluminum nitrate, aluminum isopropoxide, sodium metaaluminate, aluminum chloride, aluminum acetate, polyaluminum chloride, and aluminum sulfate 18hydrate.
[0015] In some embodiments, the ligand is a carboxylic acid ligand.
[0016] In some embodiments, the ligand is selected from a combination of one or more of 4,4',4"-(phenyl-1,3,5-trioxo)-benzoic acid, 1,4-benzenedicarboxylic acid, isophthalic acid, 2,5-furandicarboxylic acid, 2,5-pyrroledicarboxylic acid and fumaric acid.
[0017] In some embodiments, the coordination modifier is selected from an acidic coordination modifier or a basic coordination modifier.
[0018] In some embodiments, the acidic coordination modifier is selected from a combination of one or more of formic acid, acetic acid, benzoic acid and o-fluorobenzoic acid.
[0019] In some embodiments, the alkaline coordination modifier is selected from one or a combination of more than one of sodium hydroxide, sodium formate and sodium acetate.
[0020] In some embodiments, the combined mass of the aluminum salt and the ligand accounts for 4%-20% of the mass of the supersaturated solution.
[0021] In some embodiments, in the supersaturated solution, the mass ratio of the aluminum salt to the ligand is 1:1 to 1.5.
[0022] In some embodiments, the mass of the coordination modifier accounts for 1%-5% of the mass of the supersaturated solution.
[0023] In some embodiments, the solvent of the supersaturated solution is selected from one or a combination of DMF and water. Preferably, the solvent of the supersaturated solution is a mixture of DMF and water. Further preferably, in the mixture, the volume ratio of DMF to water is 3:1 to 1.5.
[0024] In some embodiments, the preparation method further comprises the step of preparing the supersaturated solution: dissolving the aluminum salt in a solvent, adding the ligand and the coordination modifier to the solvent, and stirring at room temperature to obtain the supersaturated solution.
[0025] In some embodiments, the stirring is mechanical stirring.
[0026] In some embodiments, the stirring is for 5 to 10 minutes.
[0027] In some embodiments, the low-crystalline Al-MOF aggregate layer has a thickness of 1 to 3 μm.
[0028] In some embodiments, the low-crystalline Al-MOF aggregate layer has a morphology of continuous small hills.
[0029] In some embodiments, the reaction in step 2) is carried out at 80-150°C.
[0030] In some embodiments, the reaction time in step 2) is 0.5 to 2 hours.
[0031] In some embodiments, the reaction in step 2) is carried out in a closed reactor. Preferably, the closed reactor is a polytetrafluoroethylene reactor.
[0032] In some embodiments, the crystallization reaction in step 3) is performed at 80-150°C.
[0033] In some embodiments, the crystallization reaction time in step 3) is 3 to 10 hours.
[0034] In some embodiments, the crystallization reaction in step 3) is carried out in a closed reactor. Preferably, the closed reactor is a polytetrafluoroethylene reactor.
[0035] In some embodiments, the Al-MOF seed crystal is the same as the Al-MOF crystal in the Al-MOF film material, or the Al-MOF seed crystal is the same as the Al-MOF crystal in the Al-MOF film material. That is, the seed crystal can be a seed crystal of a homologous structure, which is the same material as the MOF film prepared subsequently; or it can be a MOF crystal of a heterogeneous structure, which has the same topology and metal salt as the MOF film prepared subsequently, but a different ligand. Taking MIL-160 film as an example, the homologous seed crystal is MIL-160 nanocrystal, and the heterogeneous crystal is such as CAU-10-R and KMF-1.
[0036] In some embodiments, the Al-MOF seed crystal has a particle size of 50 to 300 nm.
[0037] In some embodiments, the deposition in step 1) is achieved by hot drop coating, spin coating, vacuum filtration or slide coating, wherein the hot drop coating includes the steps of preheating the porous support and drop coating.
[0038] Furthermore, during preheating, the porous support is heated to 80-100°C.
[0039] Furthermore, in the case of hot drop coating or spin coating, the seed dispersion is drop coated or spin coated onto the surface of the support.
[0040] Furthermore, the mass concentration of the seed crystals in the seed crystal dispersion is 0.01 to 0.015 wt.%.
[0041] In some embodiments, the Al-MOF seed layer has a thickness of 0.5 to 5 μm.
[0042] In some embodiments, the Al-MOF seed crystals are prepared by one or both of the preparation methods selected from the group consisting of a solvothermal method and a mechanical ball milling method. The mechanical ball milling method can further reduce the particle size of the seed crystals, making it easy to reach the nm level. The specific preparation method can be referred to in the literature (J.Am.Chem.Soc., 2020, 142, 6925-6929).
[0043] In some embodiments, the preparation method further comprises the steps of polishing or ultrasonically cleaning the porous support and drying the porous support before depositing the Al-MOF seed crystals.
[0044] Furthermore, the drying is vacuum drying, and preferably, the temperature of the vacuum drying is 150-200°C.
[0045] Furthermore, the grinding is performed using sandpaper, and the particle size of the sandpaper may be 600-1200 meshes.
[0046] Furthermore, the grinding time is 5 to 10 minutes.
[0047] Furthermore, the ultrasonic cleaning time is 10 to 30 minutes, and the frequency is 50 to 120 KHz.
[0048] In some embodiments, the porous support is selected from a porous alumina support or a porous polymer support.
[0049] In some embodiments, the pore size of the porous alumina support is 100-300 nm.
[0050] In some embodiments, the porous alumina support is in the form of a plate, a tube, or a hollow fiber.
[0051] In some embodiments, the porous alumina support is unmodified or modified to be surface oleophilic.
[0052] In some embodiments, the material of the porous polymer support is selected from nylon, polyacrylonitrile, polydimethylsiloxane, polyethersulfone or polyvinylidene fluoride.
[0053] In some embodiments, the Al-MOF is selected from a combination of one or more of Al-bttotb, MIL-53, CAU-10-R, CAU-23, MIL-160, KMF-1 and Al-fum.
[0054] The present invention also provides an Al-MOF membrane material prepared by the above preparation method.
[0055] The present invention also provides the use of the Al-MOF membrane material for separation of carbon dioxide / methane, carbon dioxide / nitrogen, ethylene / ethane, hexane isomers, cyclohexanol / cyclohexanone, xylene isomers, and acetic acid / water. Among them, carbon dioxide / methane, carbon dioxide / nitrogen, and propylene / propane are gas separations, while hexane isomers, cyclohexanol / cyclohexanone, xylene isomers, and acetic acid / water are liquid separations.
[0056] The present invention also provides a membrane assembly for separation, which comprises the aforementioned Al-MOF membrane material and a stainless steel support.
[0057] The assembly and preparation methods of the membrane assembly for separation all adopt existing conventional methods.
[0058] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0059] (1) The present invention utilizes a continuous low-crystalline aggregate layer to transform and grow into a dense Al-MOF film layer, which is significantly different from the most common seed-secondary growth method, which relies on the independent growth of a single seed to prepare a continuous MOF film. The transformation of the continuous layer to the continuous layer of the present invention cleverly avoids the problem of grain boundary non-symbiosis when a single seed grows independently into a film, reduces the difficulty of preparing a dense film MOF film, and realizes the universal preparation of high-valent MOF films such as Al-MOF; in addition, the transformation of the film preparation method also weakens the influence of the support structure on the film preparation to a certain extent, so that the separation performance of the MOF film is not limited by the support configuration and material, and significantly improves the application potential of MOF materials and films.
[0060] (2) The Al-MOF material prepared by the present invention is a high-valent MOF material with excellent structural stability, including water, thermal, chemical and mechanical stability, etc. The membrane material has excellent separation performance and operation stability in the molecular separation system. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 This is a SEM image of the low-crystalline MOF aggregate layer prepared in Example 1;
[0062] Figure 2 This is the XRD pattern of the low-crystalline MOF aggregate layer prepared in Example 1;
[0063] Figure 3 This is the SEM image of the Al-bttotb film prepared in Example 1;
[0064] Figure 4 XRD pattern of the Al-bttotb film prepared in Example 1;
[0065] Figure 5 This is the separation performance diagram of the Al-bttotb membrane prepared in Example 1;
[0066] Figure 6 This is the SEM image of the oriented Al-bttotb film prepared in Example 2;
[0067] Figure 7 XRD pattern of the oriented Al-bttotb film prepared in Example 2;
[0068] Figure 8 This is a separation performance diagram of the oriented Al-bttotb membrane prepared in Example 2;
[0069] Fig. 9 This is a SEM image of the tubular alumina supported Al-bttotb membrane prepared in Example 3;
[0070] Fig.10The SEM image of the PVDF-supported Al-bttotb membrane prepared in Example 4;
[0071] Fig.11 is a SEM image of the MIL-53 film prepared in Example 5;
[0072] Fig.12 XRD pattern of the MIL-53 film prepared in Example 5;
[0073] Fig.13 This is a diagram of the separation performance of the MIL-53 membrane prepared in Example 5;
[0074] Fig.14 This is a SEM image of the MIL-160 film prepared in Example 6;
[0075] Fig.15 XRD pattern of the MIL-160 film prepared in Example 6;
[0076] Fig.16 This is a diagram of the separation performance of the MIL-160 membrane prepared in Example 6;
[0077] Fig.17 This is the SEM image of the CAU-10-H membrane prepared in Example 7;
[0078] Fig.18 XRD pattern of the CAU-10-H film prepared in Example 7;
[0079] Fig.19 This is a diagram of the separation performance of the CAU-10-H membrane prepared in Example 7;
[0080] Fig. 20 This is a SEM image of the KMF-1 membrane prepared in Example 8;
[0081] Fig.21 This is a diagram of the separation performance of the KMF-1 membrane prepared in Example 8;
[0082] Fig. 22 This is the SEM image of the Al-fum film prepared in Example 9;
[0083] Fig.23 XRD pattern of the Al-fum film prepared in Example 9;
[0084] Fig.24 This is a diagram of the separation performance of the Al-fum membrane prepared in Example 9;
[0085] Fig.25 This is a SEM image of the low-crystalline MOF aggregate layer prepared in Comparative Example 1;
[0086] Figure 26-27 is the SEM image of the film prepared in Comparative Example 1;
[0087] Figure 28-30 The SEM image of low-crystalline growth and film growth of Comparative Example 2;
[0088] Figure 31-32 This is the SEM image of the film prepared in Comparative Example 3. DETAILED DESCRIPTION
[0089] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention, but the present invention is not limited to the scope of the examples.
[0090] Example 1
[0091] This embodiment provides an Al-bttotb film prepared by a low-crystalline aggregation state induction method, and the preparation steps are as follows:
[0092] (1) A porous sheet-type alumina support (pore size of 200 nm) was polished with 600-mesh and 1200-mesh sandpaper for 5 min, respectively, and then ultrasonically cleaned in a methanol solution for 15 min at an ultrasonic frequency of 50 kHz. It was then heat-treated in a vacuum drying oven at 150° C. for 2 h, and then taken out and sealed for later use.
[0093] (2) Al-bttotb nanoparticles (particle size of 150 nm) were prepared by combining the solvothermal method with the mechanical ball milling method. Specifically, the metal and ligand were added to a mixed solvent of DMF / water / formic acid (15 / 5 / 1 mL), stirred at room temperature for 30 minutes, and then transferred to a 100 mL polytetrafluoroethylene reactor, which was then transferred to an oven preset at 150°C for 1 day. After the reaction was cooled to room temperature, white crystals were obtained. The white crystals were rod-shaped crystals of 10 to 20 μm. Subsequently, 1.5 g of rod-shaped crystals and 47 g of ball-milled agate balls were added to the ball mill, and a vertical planetary ball mill XQM-12 was used to run at a rotation speed of 400 rpm for 240 minutes. The ball milled product was subjected to a 7000 rpm differential centrifugation procedure to collect spherical crystals with a particle size of about 150 nm. Subsequently, the Al-bttotb nanoparticles prepared above were dispersed in a methanol solution to obtain a seed dispersion, wherein the mass fraction of the Al-bttotb nanoparticles was 0.015 wt.%.
[0094] (3) The aforementioned seed dispersion was coated on the porous alumina support by hot drop coating. Specifically, the support was preheated to 80° C., and then 1 mL of the seed dispersion was transferred to the polished side of the support using a 1 mL pipette. After drying for 30 seconds, the above operation was repeated three times to obtain a uniform seed layer on the surface of the support.
[0095] (4) Take 0.4 g of aluminum chloride, 0.6 g of 4,4',4"-(phenyl-1,3,5-trioxo)-benzoic acid and 0.8 g of formic acid, dissolve them in 20 mL of DMF solvent to prepare a supersaturated solution, transfer the supersaturated solution to a polytetrafluoroethylene (volume ~50 mL) reactor, and then place the support with Al-bttotb nanocrystals deposited vertically in it. React at 100 °C for 1 h to convert the nanocrystal seed layer into a continuous low-crystalline MOF aggregate layer.
[0096] (5) The support with the low-crystalline MOF aggregate layer was placed vertically in a polytetrafluoroethylene (volume ~50 mL) reactor and subjected to high-temperature reaction at 150°C for 3 h to transform the low-crystalline structure into a highly ordered Al-bttotb membrane.
[0097] The low-crystalline MOF aggregate layer prepared in step (4) was tested by scanning electron microscopy (SEM) and powder X-ray diffraction (XRD). The results were as follows: Figure 1 and 2 As shown, Figure 2 In the figure, the precursor layer corresponds to the support carrier containing the low-crystalline MOF aggregate layer. It can be seen that a continuous low-crystalline MOF aggregate layer with a thickness of about 2 μm is formed on the surface of the porous alumina support.
[0098] The Al-bttotb film prepared in step (5) was subjected to scanning electron microscopy (SEM) and powder X-ray diffraction (XRD) tests (2D-XRD). The results were as follows: Figure 3 and 4 As shown, it can be seen that a high-quality Al-bttotb membrane was successfully prepared on the porous support. The surface and cross-section of the membrane were continuous, there were no grain boundary defects, and the thickness was about 10 μm.
[0099] The above Al-bttotb membrane was subjected to pervaporation separation test, and the results were as follows Figure 5 As shown (where nHex represents n-hexane, 3MP represents 3-methylpentane, and 22DMB represents 2,2-dimethylbutane), it can be seen that the membrane can efficiently separate the three-component system of hexane isomers and the cyclohexanone / cyclohexanol system, respectively. n-hexane and 3-methylpentane can pass through the membrane, while 2,2-dimethylbutane cannot. The membranes show excellent n-hexane, 3-methylpentane, and cyclohexanone permeation selectivity, respectively.
[0100] Example 2
[0101] This embodiment provides an oriented Al-bttotb membrane, and its preparation steps are basically the same as those in Example 1, except that: the porous alumina support after polishing in step (1) is subjected to surface chemical modification, and its surface properties are adjusted from hydrophilic to lipophilic: the alumina support is immersed in a 2wt.% dimethyldichlorosilane n-heptane solution, and after reacting at room temperature for 2h, the alumina support is taken out and washed with deionized water for 3 times for standby use; in addition, water is introduced into the supersaturated solution in step (4) as a co-solvent, and the volume ratio of DMF to water is 3:1, and the total volume of the two is still 20mL. Finally, a highly c-axis oriented Al-bttotb membrane is obtained.
[0102] The highly c-axis oriented Al-bttotb film was tested by scanning electron microscopy (SEM) and powder X-ray diffraction (XRD). The results are as follows: Figure 6 and 7 As shown, it can be seen that a continuous, dense and highly 1D channel-oriented Al-bttotb membrane with a thickness of about 10 μm was successfully prepared on the porous support.
[0103] The above oriented Al-bttotb membrane was subjected to pervaporation separation test, and the results were as follows Figure 8 As shown, it can be seen that the separation performance of the membrane for the three-component system of hexane isomers and the cyclohexanone / cyclohexanol system is doubled compared with the randomly oriented membrane of Example 1, especially the permeation flux of n-hexane and cyclohexanone.
[0104] Example 3
[0105] This embodiment provides an Al-bttotb membrane, and its preparation steps are basically the same as those in Example 1, except that the porous sheet-type alumina support is replaced by a porous tube-type alumina support. The SEM image of the membrane finally obtained is shown in FIG. Fig. 9 As shown, it can be seen that a high-quality continuous Al-bttotb membrane was successfully prepared, indicating that the method of the present application can be applied to a variety of support carriers and has universal applicability.
[0106] Example 4
[0107] This embodiment provides an Al-bttotb membrane, and its preparation steps are basically the same as those in Example 1, except that the porous sheet-type alumina support is replaced by a porous PVDF support. The SEM image of the membrane finally obtained is shown in FIG. Fig.10 As shown, it can be seen that a high-quality continuous Al-bttotb membrane was successfully prepared, indicating that the method of the present application can be applied to a variety of support carriers and has universal applicability.
[0108] Example 5
[0109] This embodiment provides a MIL-53 film prepared by a low-crystalline aggregation state induction method, and the preparation steps are as follows:
[0110] (1) Same as Example 1;
[0111] (2) Nano-scale MIL-53 particles with a particle size of 150 nm were prepared by solvent thermal method and mechanical ball milling method; and seed dispersion was prepared in the same manner as in Example 1.
[0112] (3) Same as Example 1.
[0113] (4) Take 0.4 g of aluminum nitrate nonahydrate, 0.6 g of 1,4-benzenedicarboxylic acid and 0.8 g of benzoic acid, dissolve them in 20 mL of DMF solvent to prepare a supersaturated solution, transfer the supersaturated solution to a polytetrafluoroethylene (volume ~50 mL) reactor, and then place the support with MIL-53 nanocrystals deposited vertically in it. React at 150 ° C for 1 hour to convert the nanocrystal seed layer into a continuous low-crystalline MOF aggregate layer.
[0114] (5) The support with the low-crystalline MOF aggregate layer was placed vertically in a polytetrafluoroethylene (volume ~50 mL) reactor and subjected to high-temperature reaction at 200 °C for 3 h to transform the low-crystalline structure into a MIL-53 membrane with a highly ordered lattice.
[0115] SEM of MIL-53 film Fig.11 and X RD Fig.12 The successful preparation of high-quality MIL-53 membrane with a thickness of about 13.8 μm was confirmed. The membrane was tested for pervaporation separation ( Fig.13 , where Flux is the flux, SF is the separation factor, and the feed concentration is the mass ratio of acetic acid to water) indicates that the membrane is capable of separating the acetic acid / water system and exhibits excellent acetic acid permeability and selectivity.
[0116] Example 6
[0117] This embodiment provides a MIL-160 film prepared by a low-crystalline aggregation state induction method, and the preparation steps are as follows:
[0118] (1) Same as Example 1;
[0119] (2) Nano-scale MIL-160 particles with a particle size of 150 nm were prepared by solvothermal method and mechanical ball milling method; and seed dispersion was prepared in the same manner as in Example 1.
[0120] (3) Same as Example 1.
[0121] (4) Take 0.4 g of aluminum chloride, 0.6 g of 2,5-furandicarboxylic acid and 0.8 g of sodium formate, dissolve them in 20 mL of DMF / water mixed solvent (the volume ratio of the two is 3:1) to prepare a supersaturated solution, transfer the supersaturated solution to a polytetrafluoroethylene (volume ~50 mL) reactor, and then place the support with MIL-160 nanocrystals deposited vertically in it. React at 100 ° C for 1 hour to convert the nanocrystal seed layer into a continuous low-crystalline MOF aggregate layer.
[0122] (5) The support with the low-crystalline MOF aggregate layer was placed vertically in a polytetrafluoroethylene (volume ~50 mL) reactor and subjected to high-temperature reaction at 100 °C for 3 h to transform the low-crystalline structure into a MIL-160 membrane with a highly ordered lattice.
[0123] The SEM of the membrane Fig.14 and X RD Fig.15 The successful preparation of high-quality MIL-160 membrane with a thickness of about 30 μm was confirmed. The membrane was tested for pervaporation separation ( Fig.16 ) showed that the membrane was capable of separating xylene isomer systems and exhibited excellent xylene permeability and selectivity.
[0124] Example 7
[0125] This embodiment provides a CAU-10-H membrane prepared by a low-crystalline aggregation state induction method, and the preparation steps are as follows:
[0126] (1) Same as Example 1;
[0127] (2) Nano-scale CAU-10-H particles with a particle size of 50 nm were prepared by a solvothermal method; and a seed dispersion was prepared in the same manner as in Example 1.
[0128] (3) Same as Example 1.
[0129] (4) Take 0.4 g of aluminum sulfate, 0.6 g of isophthalic acid and 0.8 g of sodium hydroxide, dissolve them in 20 mL of water to prepare a supersaturated solution, transfer the supersaturated solution to a polytetrafluoroethylene (volume ~50 mL) reactor, and then place the support with CAU-10-H nanocrystals deposited vertically in it. React at 100 ° C for 1 hour to convert the nanocrystal seed layer into a continuous low-crystalline MOF aggregate layer.
[0130] (5) The support with the low-crystalline MOF aggregate layer was placed vertically in a polytetrafluoroethylene (volume ~50 mL) reactor and subjected to high-temperature reaction at 100 °C for 3 h to transform the low-crystalline structure into a CAU-10-H membrane with a highly ordered lattice.
[0131] The SEM of the membrane Fig.17 and X RD Fig.18 The successful preparation of high-quality CAU-10-H membrane was confirmed. The pervaporation separation test of the membrane ( Fig.19 ) showed that the membrane was capable of separating carbon dioxide / methane, carbon dioxide / nitrogen and ethylene / ethane systems, exhibiting excellent separation selectivity, where Furley, Halp and Shimadzu respectively refer to the corresponding components tested by the detection instruments of the corresponding manufacturers.
[0132] Example 8
[0133] This embodiment provides a KMF-1 membrane prepared by a low-crystalline aggregation state induction method, and the preparation steps are as follows:
[0134] (1) Same as Example 1;
[0135] (2) Nano-scale KMF-1 particles with a particle size of 100 nm were prepared by a solvothermal method; and a seed dispersion was prepared in the same manner as in Example 1.
[0136] (3) Same as Example 1.
[0137] (4) Take 0.4 g of aluminum chloride, 0.6 g of 2,5-pyrrole dicarboxylic acid and 0.8 g of sodium hydroxide, dissolve them in 20 mL of water to prepare a supersaturated solution, transfer the supersaturated solution to a polytetrafluoroethylene (volume ~50 mL) reactor, and then place the support with KMF-1 nanocrystals deposited vertically in it. React at 80 ° C for 1 hour to convert the nanocrystal seed layer into a continuous low-crystalline MOF aggregate layer.
[0138] (5) The support with the low-crystalline MOF aggregate layer was placed vertically in a polytetrafluoroethylene (volume ~50 mL) reactor and subjected to high-temperature reaction at 80 °C for 3 h to transform the low-crystalline structure into a KMF-1 membrane with a highly ordered lattice.
[0139] The SEM of the membrane Fig. 20 The successful preparation of high-quality KMF-1 membrane was confirmed. The membrane was tested for pervaporation separation ( Fig.21 ) showed that the membrane was able to separate the hexane isomer system and exhibited excellent separation selectivity.
[0140] Example 9
[0141] This embodiment provides an Al-fum film prepared by a low-crystalline aggregation state induction method, and the preparation steps are as follows:
[0142] (1) Same as Example 1;
[0143] (2) Nano-scale Al-fum particles with a particle size of 100 nm were prepared by a solvothermal method; and a seed dispersion was prepared in the same manner as in Example 1.
[0144] (3) Same as Example 1.
[0145] (4) Take 0.4 g of sodium aluminate, 0.6 g of fumaric acid and 0.8 g of sodium acetate, dissolve them in 20 mL of DMF / water mixed solvent (the volume ratio of the two is 3:1) to prepare a supersaturated solution, transfer the supersaturated solution to a polytetrafluoroethylene (volume ~50 mL) reactor, and then place the support with Al-fum nanocrystals deposited vertically in it. React at 120 ° C for 1 hour to convert the nanocrystal seed layer into a continuous low-crystalline MOF aggregate layer.
[0146] (5) The support with the low-crystalline MOF aggregate layer was placed vertically in a polytetrafluoroethylene (volume ~50 mL) reactor and subjected to high-temperature reaction at 100 °C for 3 h to transform the low-crystalline structure into a highly ordered Al-fum film.
[0147] The SEM of the membrane Fig. 22 and X RD Fig.23 The successful preparation of high-quality Al-fum membrane with a thickness of about 10 μm was confirmed. The membrane was tested for pervaporation separation ( Fig.24 ) showed that the membrane was able to separate the hexane isomer system and exhibited excellent n-hexane separation selectivity.
[0148] Comparative Example 1
[0149] The method is basically the same as Example 1, except that in step (4), 0.4 g of aluminum chloride, 0.6 g of 4,4',4"-(phenyl-1,3,5-trioxo)-benzoic acid and 0.8 g of formic acid are replaced by 0.08 g of aluminum chloride, 0.06 g of 4,4',4"-(phenyl-1,3,5-trioxo)-benzoic acid and 0.8 g of formic acid, respectively, and the prepared solution is unsaturated. The prepared low-crystalline MOF aggregate and Al-bttotb film were subjected to scanning electron microscopy (SEM) testing, and the results are as follows: Figure 25-27 As shown, the low-crystalline Al-MOF aggregates appear discontinuous on the surface of the porous support ( Fig.25 ), and the resulting film also has obvious grain boundary defects ( Figure 26-27 ).
[0150] Comparative Example 2
[0151] The method is basically the same as Example 1, except that formic acid is not added in step (4), that is, no coordination regulator is added to the supersaturated solution. The low crystal growth and film growth were tested by scanning electron microscope (SEM), and the results are shown in the figure ( Figure 28-30 ), it can be seen that no low-crystalline Al-MOF aggregates were obtained on the surface of the porous support ( Fig.28 ), so it cannot be used to transform into a highly ordered Al-bttotb film ( Figure 29-30 ).
[0152] Comparative Example 3
[0153] Preparation of Al-bttotb film by ordinary secondary seed growth method:
[0154] Steps (1)-(3): same as in Example 1;
[0155] Step (4): 0.08 g of aluminum chloride, 0.12 g of 4,4',4"-(phenyl-1,3,5-trioxo)-benzoic acid and 0.8 g of formic acid were prepared into a reaction solution, and the reaction solution was transferred to a polytetrafluoroethylene (volume ~ 50 mL) reactor, and the support body with the Al-bttotb nanocrystals deposited was directly placed vertically therein, and reacted at a high temperature of 150°C for 12 hours. The prepared Al-bbttob film was subjected to a scanning electron microscope (SEM) test, and the results were as follows: Figure 31-32 As shown, it can be seen that a continuous Al-bttotb film layer is obtained, but there are too many intercrystalline gaps and the morphology is irregular.
[0156] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an Al-MOF membrane material, characterized in that: The preparation method comprises the following steps: 1) depositing Al-MOF seed crystals on the surface of a porous support to obtain an Al-MOF seed crystal layer; 2) placing the porous support with the Al-MOF seed crystal layer deposited on the surface in a supersaturated solution to react and grow a continuous low-crystalline Al-MOF aggregate layer on the surface of the porous support; 3) subjecting the porous support with the continuous low-crystalline Al-MOF aggregate layer grown on the surface to a crystallization reaction to obtain the Al-MOF membrane material; the supersaturated solution comprises an aluminum salt, a ligand and a coordination regulator.
2. The method for preparing the Al-MOF membrane material according to claim 1, characterized in that: The aluminum salt is selected from a combination of one or more of aluminum nitrate, aluminum isopropoxide, sodium aluminate, aluminum chloride, aluminum acetate, polyaluminum chloride and aluminum sulfate 18hydrate; and / or, the ligand is a carboxylic acid ligand, preferably, the ligand is selected from a combination of one or more of 4,4',4"-(phenyl-1,3,5-trioxo)-benzoic acid, 1,4-benzenedicarboxylic acid, isophthalic acid, 2,5-furandicarboxylic acid, 2,5-pyrroledicarboxylic acid and fumaric acid; and / or, the coordination regulator is selected from an acidic coordination regulator or a basic coordination regulator, preferably, the acidic coordination regulator is selected from a combination of one or more of formic acid, acetic acid, benzoic acid and o-fluorobenzoic acid; the basic coordination regulator is selected from a combination of one or more of sodium hydroxide, sodium formate and sodium acetate.
3. The method for preparing the Al-MOF membrane material according to claim 1, characterized in that: The total mass of the aluminum salt and the ligand accounts for 4%-20% of the mass of the supersaturated solution; and / or, in the supersaturated solution, the mass ratio of the aluminum salt and the ligand is 1:1-1.5; and / or, the mass of the coordination regulator accounts for 1%-5% of the mass of the supersaturated solution; and / or, the solvent of the supersaturated solution is selected from one or a combination of DMF and water.
4. The method for preparing the Al-MOF membrane material according to claim 1, characterized in that: The preparation method further comprises the step of preparing the supersaturated solution: dissolving the aluminum salt in a solvent, adding the ligand and the coordination regulator into the solvent, and stirring at room temperature to obtain the supersaturated solution.
5. The method for preparing the Al-MOF membrane material according to claim 1, characterized in that: The thickness of the low-crystalline Al-MOF aggregate layer is 1 to 3 μm.
6. The method for preparing the Al-MOF membrane material according to claim 1, characterized in that: The reaction in step 2) is carried out at 80-150° C.; and / or, the reaction time in step 2) is 0.5-2 h; and / or, the reaction in step 2) is carried out in a closed reactor.
7. The method for preparing the Al-MOF membrane material according to claim 1, characterized in that: The crystallization reaction in step 3) is carried out at 80-150° C.; and / or, the crystallization reaction time in step 3) is 3-10 hours; and / or, the crystallization reaction in step 3) is carried out in a closed reactor.
8. The method for preparing the Al-MOF membrane material according to claim 1, characterized in that: The Al-MOF seed crystal is the same as the Al-MOF crystal in the Al-MOF membrane material, or the Al-MOF seed crystal has the same topological structure as the Al-MOF crystal in the Al-MOF membrane material; and / or, the particle size of the Al-MOF seed crystal is 50 to 300 nm; and / or, the deposition in step 1) is achieved by hot drop coating, spin coating, vacuum filtration or slide coating, wherein the hot drop coating method includes the steps of preheating the porous support and the drop coating step; and / or, the thickness of the Al-MOF seed crystal layer is 0.5 to 5 μm.
9. The method for preparing the Al-MOF membrane material according to claim 1, characterized in that: The Al-MOF seed crystals are prepared by one or both of the preparation methods selected from the group consisting of a solvothermal method and a mechanical ball milling method; and / or, the preparation method further comprises the steps of polishing or ultrasonically cleaning the porous support and drying the porous support before depositing the Al-MOF seed crystals.
10. The method for preparing the Al-MOF membrane material according to claim 1, characterized in that: The porous support is selected from a porous alumina support or a porous polymer support; preferably, the pore size of the porous alumina support is 100-300 nm, and the porous alumina support is plate-type, tubular-type or hollow fiber-type; the material of the porous polymer support is selected from nylon, polyacrylonitrile, polydimethylsiloxane, polyethersulfone or polyvinylidene fluoride.
11. The method for preparing the Al-MOF membrane material according to claim 1, characterized in that: The Al-MOF is selected from one or more combinations of Al-bttotb, MIL-53, CAU-10-H, CAU-23, MIL-160, KMF-1 and Al-fum.
12. An Al-MOF membrane material prepared by the preparation method according to any one of claims 1 to 11 (the thickness of the membrane is 3 to 20 μm).
13. Use of the Al-MOF membrane material according to claim 12 for separation of carbon dioxide / methane, carbon dioxide / nitrogen, ethylene / ethane, hexane isomers, cyclohexanol / cyclohexanone, xylene isomers, and acetic acid / water.
Citation Information
Patent Citations
Preparation method of metal organic framework MOF-2 polycrystalline film
CN103820850A
MOF-802 separation membrane, preparation method and application of MOF-802 separation membrane in H2 purification
CN117046320A
Method for preparing defect-free MOF (Metal Organic Framework) film in MOF gradient distribution seeding mode
CN117101424A
Method for preparing hierarchical pore structure metal-organic framework film composite film
CN118059698A
Metal organic frameworks and methods of making and using same
US20190217270A1